Memecahkan Resiko Usaha: Strategi Pemasaran Perajin Jadah Tempe Skala Mikro Dari Kaliurang - Bambang Hudayana; Kartika Rini (IAI Nasional Laa Roiba Bogor, 2025)
Kaliurang has a very iconic traditional food called jadah tempe and can only be found in this tourist area. However, now many tempeh products which are classified as MSMEs are bought and sold outside the area. Business problems and marketing strategies are the objectives that want to be uncovered to find out the causes of the widespread sales of this traditional food. This research uses a formalist economic anthropology perspective with qualitative methods. The result is that as a tourist destination as well as a disaster-prone area of ​​Merapi, the problems faced by Kaliurang jadah tempeh craftsmen are more complex than MSMEs in general. As a result, tight business competition due to reduced sources of income cannot be avoided. The eruption of Merapi has had a degrading impact on visitors. This problem is correlated with the marketing strategy implemented. Diffusion is the main strategy for craftsmen to solve business risks. Furthermore, it is effective in expanding market share and increasing revenue.